Karakteristik Pasien Otitis Media Supuratif Kronik di RSUP Haji Adam Malik Medan - Ayu Debora Nainggolan; Ridwan Balatif (Majalah Kedokteran Andalas, 2021)
Objective: Knowing the current picture regarding the profile of patients with chronic suppurative otitis media (CSOM) at Haji Adam Malik General Hospital Medan.  Method: This study is a descriptive study to get an overview of CSOM patients at the Haji Adam Malik General Hospital. The sampling technique in this study used total sampling. Data on CSOM patients were taken from medical records. Samples that meet the criteria for inclusion in this study are CSOM patients with complete medical records. Results: A total of 130 CSOM patient data were included in this study. The majority of CSOM patients are in the age range of 11-20 years and 21-30 years, each with 33 patients (25.4%). Most of the patients were male (63.1%) and did not work (55.4%). The main complaint of most CSOM patients in this study was otorrhoea (36.9%) and 63.8% of CSOM cases were benign. About 20.8% of CSOM patients had no complications and the most treatment for CSOM patients was collapsed wall tympanomastoidectomy (36.2%). Conclusion: The description of CSOM patients at Haji Adam Malik Hospital Medan has a similar picture with CSOM patients in general.